CRASHWORTHINESS INVESTIGATION OF VEHICLE FRONT BUMPER BEAM WITH DIFFERENT CROSS-SECTIONS UNDER AXIAL DYNAMIC LOAD - Beytüt, Hüseyin; Karagoz, Selçuk; Özel, Serkan (My University, 2020)
Bumper beam, is one of the first structures exposed to impact at the time of an accident. Therefore, how it behaves at the time of an accident is extremely important in terms of passenger safety, cargo and other critical parts of the vehicle. What is expected from a bumper beam is to absorb the kinetic energy of the vehicle through plastic deformation, particularly at low and medium speeds. In this study, finite element models of the crash situations of the bumper beams with five different cross-sectional geometries and equal weights were created by using the HyperMesh software and crash analyses were carried out. Since the bumper beams may behave differently in different barrier types, pole and wall barrier impact test was investigated. AA6061-T6 Aluminum alloy was used as the material and Johnson-Cook was used as the material model. The results revealed that the cross-sectional geometry had significant effect on crashworthiness and the models exhibited different crashworthiness on wall and pole barriers. RADIOSS/explicit and non-linear finite element codes were used.
Keywords: Mühendislik; Makine